Comparative Evaluation of Flexural Strength of Heat-Polymerized Polymethyl Methacrylate Denture Base Material Reinforced with Silanized Aluminium Oxide Nanoparticles and Silanized Tetragonal Zirconium Oxide Nanoparticles – An In Vitro Study - Richa Sahai; Sumeet Jalan (Journal of International Clinical Dental Research Organization)
Background: Polymethyl methacrylate (PMMA) is the most widely used material in denture fabrication in prosthodontics. Despite its popularity which satisfies esthetics, simple processing, and easy repair, the common problems associated with PMMA as a denture base material are poor strength, lack of radio-opacity, poor flexural and impact strength, liable to fracture, and poor thermal conductivity. Thus, this study was conducted to compare and evaluate the flexural strength (FS) of heat-polymerized PMMA denture base material reinforced with silanized aluminum oxide nanoparticles and silanized tetragonal zirconium oxide nanoparticles. Therefore, this research was carried out to compare and evaluate the FS of heat-polymerized PMMA denture base material reinforced with silanized aluminum oxide nanoparticles and silanized tetragonal zirconium oxide nanoparticles. Materials and Methods: In addition to the controlled group of heat-cured PMMA, the silanized (Al2O3) nanoparticles and silanized tetragonal zirconium oxide nanoparticles were added to PMMA powder by weight and mixed by probe ultrasonication machine. Ninety samples were fabricated and divided into three groups (each group consist of 30 samples). The tests conducted were to check the FS of reinforced PMMA. The results were statistically analyzed using one-way analysis of variance and Tukey’s post hoc test. Results: There was a statistical significance between the heat polymerized acrylic resin denture base samples reinforced with 1% silanized aluminum oxide nanoparticles (Group A) and 3% silanized tetragonal zirconium oxide nanoparticles (Group Z) and they increased the FS compared to the control group. Conclusion: Samples with reinforcement increase the FS. Reinforcement with both 1% silanized aluminum oxide nanoparticles and 3% silanized tetragonal zirconium oxide nanoparticles showed a highly significant increase in FS compared with the control group.